Responsible leadership and ethical decision-making. - Savur, Sunil; Sandhu, Sukhbir (Research in ethical issues in organizations ;, 2017)
The volume brings to life a number of the conference themes including corporate social responsibility, culture, academic integrity, vulnerability, health, military ethics, education, leadership, sustainability and philosophy and addresses concerns of many leading applied ethicists.